Cancer-control outcomes of Radium-223-pretreated lutetium- 177-PSMA radioligand vs. Radium- 223-naïve mCRPC patients - Wenzel, Mike; Theissen, Lena; Groener, Daniel; Kriegmair, Maximilian; Graefen, Markus; Maurer, Tobias; Salomon, Georg; Hoeh, Benedikt; Siech, Carolin; Banek, Severine; Chun, Felix K. H.; Mandel, Philipp (European journal of nuclear medicine and molecular imaging, 2025)
Purpose Radium- 223 and Lutetium- 177 prostate-specific membrane antigen radioligand therapy (Lu- 177-PSMA) are approved for the treatment of patients with metastatic castration-resistant prostate cancer (mCRPC). Data on cancer-control outcomes of sequential therapy of Lu- 177-PSMA after radium- 223 are rare. Methods Using the Frankfurt Metastatic Cancer database of the Prostate (FRAMCAP) database, we analyzed progression-free (PFS) and overall (OS) survival of patients after radium- 223 pretreatment vs. radium- 223-naïve controls undergoing Lu- 177-PSMA radioligand within 1 st- 7 th line mCRPC treatment. Results Of 329 Lu- 177-PSMA mCRPC patients 19% were radium- 223 pretreated, while 81% radium- 223-naïve. The median number of administered mCRPC systemic treatment administrations were significantly higher for radium- 223 pretreated patients (4 vs. 3, p < 0.01). No difference in further baseline or cancer characteristics were observed, similar to PSA response under Lu- 177-PSMA treatment. In PFS analyses, no significant difference between radium- 223 pretreated vs. radium- 223-naïve Lu- 177-PSMA mCRPC patients were observed, with median PFS of 16 vs. 12 months (hazard ratio [HR]: 0.73, confidence interval [CI]: 0.52-1.02, p = 0.063). In OS analysis, also no significant differences were observed with median OS of 18 vs. 15 months for radium- 223 pretreated vs. radium- 223-naïve Lu- 177-PSMA mCRPC patients (HR: 0.99, CI: 0.71-1.37, p > 0.9). Finally, after additional multivariable adjustment, no differences in PFS and OS outcomes between both groups were observed. Conclusion Sequential treatment with radium- 223 prior to Lu- 177-PSMA does not affect PFS or OS outcomes in mCRPC patients. Therefore, this real-world cohort suggests that both radiopharmaceuticals can be administered within mCRPC treatment algorithm.
Gesehen am 01.07.2025